Connecting Concepts and Representations in Mathematics: A Sistematic Literature Review - Latifa, Ulfa; Indrasari, Peti; Pramuditya, Surya Amami; Asnawati, Sri (International Journal of Contemporary Studies in Education, 2025)
Purpose - This study aims to identify effective media, instructional strategies, or teaching models that can bridge conceptual understanding and mathematical representation in mathematics education. It was motivated by the persistent gap observed between students' conceptual grasp and their ability to translate concepts into mathematical forms, which hinders problem-solving competence. Methodology - A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines. Literature was sourced from Google Scholar and DOAJ databases, focusing on publications from 2015 to 2025. The review process resulted in seven articles meeting the inclusion criteria. Data analysis involved thematic synthesis of instructional approaches and their reported effectiveness in bridging conceptual and representational understanding. Findings - The review found that the relationship between conceptual understanding and mathematical representation is closely linked but not automatic, depending significantly on the instructional strategies employed. Effective approaches identified include the Concrete–Pictorial–Abstract (CPA) model, GeoGebra media, SAVI strategy, Joyful Problem-Based Learning (JPBL), and Role-Playing Game (RPG)-based learning, which enhance engagement and facilitate conceptual-visual connections. These findings imply the need for intentional instructional designs that integrate conceptual and representational aspects in mathematics learning. Novelty - This study contributes by systematically mapping and synthesising diverse strategies and media specifically targeting the integration of conceptual understanding with mathematical representation, an area underexplored in prior reviews. Significance - The results are valuable for mathematics educators, curriculum developers, instructional designers, and educational policymakers seeking evidence-based practices to improve mathematics teaching and learning outcomes.